LEGAL PROTECTION OF SMART CONTRACT IN INDONESIA WITH REFERENCE TO DUTCH LAW - Cut Putroe Salsabila; Eka Kurniasari (Student Journal of International Law, 2023)
The growth of technology has altered many human habits, including business practices. One ofthe emerging innovations is smart contracts. However, Indonesia still has not possessed specificregulations toward smart contract. This article investigates the legalprotection for the execution of smart contracts in Indonesia with reference to the Dutch General Data Protection Regulation (GDPR). The research methodology used in this thesis is normative research, namely legal research conducted by examining library materials or secondary legal materials, and tertiary legal materials. The article shows that the issue with present Indonesian law is that it fails to acknowledge the potential benefits and drawbacks of smart contracts. Hence setting up a specific law to regulate smart contract protection and its implementation, including the protection of the data subject, as well as the safeguard measures is urgently required.